A Road and a Forest: Conceptions of In‐Class and Out‐of‐Class Learning in the Transition to Study Abroad. Issue 4 (19th September 2017) - Kashiwa, Mayumi; Benson, Phil
Abstract : Adopting an ecological perspective on context in second language learning, this study investigated the ways in which a group of Chinese students reconceptualized and reconstructed their learning environments in the first 3 months of study abroad in Australia. Focusing on the students' conceptions of the relationship between in‐class and out‐of‐class learning, the study identified a shift from a view that the two contexts were separated in study at home to a more integrated view in study abroad. However, this was a variable process, with some students adapting more quickly than others and some barely changing their conceptions at all. The study also found a relationship between students' awareness of the affordances of the study abroad setting and their agency in creating opportunities for out‐of‐class learning. It is suggested that teachers can help enhance study abroad participants' awareness and agency by allocating class time to discussion of their out‐of‐class learning experiences and by connecting classroom instruction to the world beyond the classroom.